The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1089/ars.2013.5373
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy: A Crucial Moderator of Redox Balance, Inflammation, and Apoptosis in Lung Disease

Abstract: Significance: Autophagy is a fundamental cellular process that functions in the turnover of subcellular organelles and protein. Activation of autophagy may represent a cellular defense against oxidative stress, or related conditions that cause accumulation of damaged proteins or organelles. Selective forms of autophagy can maintain organelle populations or remove aggregated proteins. Autophagy can increase survival during nutrient deficiency and play a multifunctional role in host defense, by promoting pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 201 publications
(299 reference statements)
1
64
0
Order By: Relevance
“…These data suggests a dynamic restoration of the mitochondrial population through quality control mechanisms. Autophagy is essential for this process since it removes damaged cytosolic and mitochondrial organelles, which are sequestered and delivered to lysosomes for degradation and recycling [24, 48, 49]. Proteins or organelles modified by reactive species are targeted for removal by the lysosomal-autophagy system and the selective removal of mitochondria by mitophagy is a critical step in maintaining mitochondrial quality control [1, 24, 25, 32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggests a dynamic restoration of the mitochondrial population through quality control mechanisms. Autophagy is essential for this process since it removes damaged cytosolic and mitochondrial organelles, which are sequestered and delivered to lysosomes for degradation and recycling [24, 48, 49]. Proteins or organelles modified by reactive species are targeted for removal by the lysosomal-autophagy system and the selective removal of mitochondria by mitophagy is a critical step in maintaining mitochondrial quality control [1, 24, 25, 32].…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable debate as to whether autophagy contributes to or mitigates the pathology of pulmonary disease [24, 48]. For example, Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The balance between apoptosis and autophagy has been recognized to be essential in the determination of the life span of macrophages within the inflammatory context. 16 In recent years it has become evident that both processes exhibit substantial molecular crosstalk that is not yet fully understood. 17 We have demonstrated that LXA 4 increases macrophage survival via inhibition of the apoptotic process.…”
Section: Introductionmentioning
confidence: 99%
“…[36,56,77,78] and other physiological/pathophysiological processes, such as development, differentiation [42], anti-aging, elimination of microorganisms, cell death, tumor suppression and antigen presentation in the body [14,48]. In responses to stress, the primary function of autophagy is thought to aid cellular survival by recycling damaged organelles and misfolded proteins to provide energy and substrates for reconstruction [44].…”
Section: Major Functions Of Autophagymentioning
confidence: 99%